Research on the Impact of Digital Economy on Urban Green Total Factor Productivity - Chen, Jifeng; Li, Dongsheng (International Journal of Global Economics and Management, 2024)
In order to reveal the inherent mechanism of the role of the digital economy in urban green total factor productivity, and provide policy recommendations for achieving the development of the digital economy and urban green development. This article is based on panel data from 274 prefecture level and above cities in China from 2011 to 2020, and empirically analyzes the possible impact and mechanism of the digital economy on urban green total factor productivity. The research results indicate that: (1) the development of the digital economy can promote the improvement of urban green total factor productivity, and for non resource-based cities, high administrative level cities, and southern cities, the role of digital economy in empowering urban green total factor productivity is more significant; (2) The mechanism test shows that the development of digital economy can enhance the level of green innovation, achieve industrial structure upgrading, and thereby improve urban green total factor productivity. In addition, the impact of the digital economy on urban green total factor productivity is constrained by the threshold effect of industrial structure upgrading.